IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA PADA PESERTA DIDIK MADRASAH IBTIDAIYAH AS’ADIYAH NO. 3 SENGKANG PERSPEKTIF ILMU JIWA - Subhan, Nuraini; Nurul Intan, Magfira; Khatimah, A. Khusnul; Hunaifi, Ilham; Mukarrama, Amalia; Mutmainnah, Besse; Santalia, Indo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of religious moderation values among students at Madrasah Ibtidaiyah As'Adiyah No. 3 Sengkang based on a psychology perspective. The study used qualitative methods through literature studies combined with observation, and interviews. The results showed that religious moderation values have been consistently applied through religious habits, learning activities, and social interactions within the madrasah environment. Students demonstrate tolerance, respect for differences in beliefs, are able to resolve conflicts peacefully, and work together regardless of religious background. From a psychology perspective, the application of religious moderation values contributes to cognitive, affective, and psychomotor development, while also forming a moderate, empathetic, and inclusive personality. These findings emphasize the importance of the role of teachers as role models and the effectiveness of religious habits as a basis for character formation since elementary education.